Preparation and Characterization of Iron based Indian traditional drug Abhrak Bhasma - Pathak, Richa (International Journal of Pharmaceutical & Biological Archive, 2015)
Preparation and Characterization of Iron based Indian traditional drug Abhrak Bhasma